PERAN PUSTAKAWAN DALAM MENUMBUHKAN MINAT BACA DI ERA DIGITAL - Nur Sanny Rahmawati (Ikatan Pustakawan Indonesia, 2018)
This study discusses the role of librarians to increase reading interest in the digital era. The purpose of this study is to identify the things which should be done by librarians to build a reading culture in the present. This research is using qualitative method. Literature review is a research approach which is used to obtain descriptive analysis. The results of this study note that to build interest in reading in the digital era, librarians must be able to identify the needs of users, increase the availability of quality collections, build communication with the government, and participate in professional organizations to improve their competence.